P-24 Documentation and discussion of advance care planning in an acute hospital: A review of the medical records of patients approaching the end of life. (1st September 2015) - Malyon, AC; Forman, J; McFritz, ZB
Abstract : Background: Around 78% of individuals are admitted to hospital at least once (average 2.1 admissions) in their last year of life. Aim: To examine the incidence of documentation of advance care planning (ACP) in the hospital medical records of patients approaching the end-of-life. To explore the impact of a new approach to recording treatment decisions, the Universal Form of Treatment Options (UFTO), on the incidence of ACP. Methods: Retrospective review of hospital medical records of patients who died within 90 days of admission to the oncology or respiratory wards in a UK University Hospital. Data collected over three-month periods on incidence of documentation of advance care discussions or decisions before and after the introduction of the UFTO. Results: Of the 81 patients who died within 90 days of admission in the pre-UFTO group, only 23 had an ACP discussion documented. 44 had decisions about cardiopulmonary resuscitation (CPR) recorded. Introduction of the UFTO was associated with a statistically significant increase (p = 0.01) in decisions regarding CPR in oncology but not respiratory patients. There was no significant impact on the documentation of other decisions about future care. Only one patient had a recognised ACP document. Discussion: Despite patients' proximity to the end-of-life, there was limited documentation of treatment preferences and almost no evidence of formalised ACP in hospital medical records. Conclusion: Further work is needed to improve discussion and documentation of ACP to ensure patients' preferences for treatment are known and respected if they are admitted to hospital near to the end-of-life.